DAMPAK KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DI MAL PELAYANAN PUBLIK KOTA TANJUNGPINANG - Viona Pramesty Eka Putri; Fitri Kurnianingsih; Imam Yudhi Prastya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the impact of service quality on community satisfaction at the Public Service Mall of Tanjungpinang City. The research uses a descriptive qualitative approach with the main theory of Expectation Disconfirmation Theory by Oliver and the supporting theory of SERVQUAL, which includes the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. Data collection techniques were conducted through interviews, observations, and documentation involving service users, Public Service Mall employees, and the DPMPTSP of Tanjungpinang City as informants. Data analysis used the interactive model of Miles and Huberman through data reduction, data presentation, and conclusion drawing. The results indicate that the service quality at the Public Service Mall of Tanjungpinang City has generally met community expectations and contributed to community satisfaction. This is reflected in the dimensions of tangibles, reliability, responsiveness, assurance, and empathy, which are demonstrated through relatively prompt services, courteous staff, adequate facilities, and easy access to public services. However, several challenges remain, including waiting times for certain services and procedures that are perceived as relatively complicated. Therefore, good service quality contributes to enhancing community satisfaction, trust, and comfort in utilizing public services.